👤
a fost răspuns

Sa se arate ca dacă x+y=z atunci:

cos^2 x + cos^2 y + cos^2 z - 2cos x cos y cos z = 1


Răspuns :

x+y=z Se aplica sin
[tex]sin(x+y)=sin(z)[/tex]
[tex]sinx*cosy+siny*cosx=sinz[/tex] Se ridica la patrat
[tex] sin^{2}x* cos^{2}y+ sin^{2}y* cos^{2}x+2sinx*cosy*siny*cosx= sin^{2}z[/tex]
[tex](1- cos^{2}x)cos^{2}y+(1- cos^{2}y)cos^{2}x+2sinx*cosy*siny*cosx=[/tex]
[tex]1- cos^{2}z[/tex]
[tex] cos^{2}y- cos^{2}x * cos^{2}y+ cos^{2}x- cos^{2}x * cos^{2}y[/tex]+
[tex]2sinx*siny*cosx*cosy=1- cos^{2}z [/tex]
[tex] cos^{2}x+ cos^{2}y+ cos^{2}z-2*cosx*cosy*(cosx*cosy-sinx*siny)[/tex]
=1
[tex]cos^{2}x+ cos^{2}y+ cos^{2}z-2*cosx*cosy*cos(x+y)[/tex]
=1
[tex]cos^{2}x+ cos^{2}y+ cos^{2}z-2*cosx*cosy*cosz[/tex]
=1